'It stopped you thinking about food' – The experiences of mealtimes and attending a post‐meal support group for young people with anorexia nervosa. (9th September 2022) - Monaghan, Margaret; Doyle, Louise
Abstract: Anorexia nervosa presents as an international public health concern as it is the mental health problem with the greatest risk of mortality, and the average age of onset is decreasing. For those experiencing anorexia nervosa, mealtimes have long been recognized as a difficult and distressing time when young people need additional support. However, the post mealtime period can be associated with even greater distress, yet there is little research on interventions to support young people in this vulnerable time, and even less on how young people experience these interventions. This study, therefore, explores young peoples' perceptions of mealtimes and a post mealtime support group. Using a qualitative descriptive design, telephone interviews were conducted with a purposive sample of six young people who participated in a post‐meal support group while an inpatient in a Child and Adolescent Mental Health Unit. Using a semi‐structured interview guide, participants were asked about their experiences of this support group and their perceptions of how to improve this intervention. Content analysis resulted in the development of three themes: 'The Challenges of Mealtimes and Post Mealtimes', 'The Benefits of Post‐meal Support Groups', and 'Improving Unhelpful Aspects of Post‐meal Support Groups'. Findings are reported in accordance with COREQ guidelines and suggest that for young people experiencing anorexia nervosa, post mealtimes are often more distressing than the meal itself and that participants found post‐meal support groups to be a helpful intervention in reducing post‐mealtime distress. Post‐meal support groups can be improved by ensuring a consistent approach from staff and providing staff with the training and knowledge required to support those affected by eating disorders.